Implementation Of DKI Jakarta Regulation Number 7 Of 2010 Concerning Building Construction Of Boarding Houses In Tanjung Duren Sub-District, West Jakarta (Indonesian Journal of Agrarian Law, 2026)
This study examines the implementation of DKI Jakarta Provincial Regulation Number 7 of 2010 concerning Building Construction in controlling the construction of unlicensed boarding houses in Tanjung Duren Village, West Jakarta. Problems arise because although the regulation requires every building to have a Building Construction Permit (PBG), in practice many boarding house owners still build without complying with applicable licensing procedures. This study aims to analyze the effectiveness of the regulation's implementation and identify factors that cause community non-compliance with building permit obligations. The research method used is an empirical juridical approach with a statutory regulatory approach and a sociological approach through document studies, observations, and interviews with relevant informants. The results show that the implementation of the regulation has not been effective. Law enforcement tends to be reactive and administrative, such as imposing fines, without being followed by firm preventive or repressive measures. In addition, weak inter-agency coordination, limited supervision, and the complexity of the licensing process also contribute to the low level of community compliance. This study contributes to providing an empirical picture of the gap between legal norms and community practices in controlling boarding house construction. Therefore, it is necessary to increase the socialization of regulations, simplify licensing procedures, and strengthen supervision by local governments so that the implementation of regulations can run more effectively.